O centro cultural como equipamento disseminador de informação: um estudo sobre a ação do Galpão Cine Horto - Luciene Borges Ramos (2007)
This study examines the role of cultural centers in the Information Society, highlighting their function as disseminators of information. First, a review of the literature was made to define the terms information and culture. These two concepts were explained, noting the close relation that exists between them in contemporary society. Next, a historical and conceptual review of cultural centers was presented, examining aspects of their origin and clarifying their relation with traditional public libraries. The importance of information for the practice of cultural actions at theseplaces was emphasized, and different models of cultural centers in Brazil and throughout the world were presented in order to give a broad understanding of the activities developed by these entities. A case study focusing on the Galpão Cine Horto cultural center was presented. The study examined the centers historical dimension and the cultural action developed through a wide variety of artistic and informational projects. Data on the informative work carried out at the Galpão Cine Horto was collected and analyzed to identify aspects of the dissemination and use of information in the context of cultural centers, and to determine the relevance of the institution from the standpoint of the information it disseminates to its users. The results obtained highlight how cultural actions are presently based on the information, and at the same time, stimulate other actions with an informational nature. In this context, cultural centers become the stage for actions focused on the production,preservation, dissemination and use of information.